2009
DOI: 10.5539/ijbm.v4n2p142
|View full text |Cite
|
Sign up to set email alerts
|

Non-Audit Service and Audit Independence: Evidences from Iran

Abstract: From recent years on, because of several reasons independence of auditor became undermined, so far some factors recognized that which impair independence, especially non-audit service so, in this condition may appear to affect to independence. The results of this study show that shareholders strongly agree that providing NAS by external auditors to the same clients strongly negatively affect to audit independence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The companies have increasingly turned to providing customers with far more profitable non audit services, and especially for the big firms, which some estimate now receive 30% to 40% of their revenues from non-audit services (Walker, 1999). Overall, many researchers argue that NAS weaken objectivity, as well as independence, whereas others found that there exists no association between NAS and audit quality (Frankel et al, 2002;Kilgore, 2007;Salehi, 2009). Defond et al, (2002) have observed that, researchers are concerned about two effects of NAS.…”
Section: Provision Of Non-audit Services (Nas)mentioning
confidence: 99%
“…The companies have increasingly turned to providing customers with far more profitable non audit services, and especially for the big firms, which some estimate now receive 30% to 40% of their revenues from non-audit services (Walker, 1999). Overall, many researchers argue that NAS weaken objectivity, as well as independence, whereas others found that there exists no association between NAS and audit quality (Frankel et al, 2002;Kilgore, 2007;Salehi, 2009). Defond et al, (2002) have observed that, researchers are concerned about two effects of NAS.…”
Section: Provision Of Non-audit Services (Nas)mentioning
confidence: 99%
“…Secondly, this study is also motivated by recent changes in professional standards related to auditor independence in Iran in a bid to increase our understanding of the similarities and differences compared to IFAC code of independence and other threats identified in the literature (Kosmala, 2007;Lee & Stone, 1995;Ramazani & Atani, 2010;Salehi & Husini, 2011). This study is also driven by the mixed, if not, conflicting results in the literature on threats to independence in Iran (MohammadRezaei, Mohd-Saleh, Jaffar, & Hassan, 2016;Salehi, 2009aSalehi, , 2009bSalehi et al, 2009a). As advanced by Salehi (2009a), there is yet no clear evidence on auditor independence in Iran.…”
Section: Introductionmentioning
confidence: 89%
“…Accounting service can be any service, other than audit, provided by an accounting firm to a client. Public accounting firms expanded the scope of their services to include corporate and individual tax planning, internal audit outsourcing and consulting related to mergers and acquisitions, information system (Salehi, 2009). It is argued by many researchers that it is more economical for accounting firms to provide other additional services to their clients, since the auditor has a good knowledge of their client's business (Islam, Karim and Van-Zijil, 2005).…”
Section: Accounting Servicesmentioning
confidence: 99%
“…Accountants provide variety of services aimed at meeting the needs of their clients. Okezie (2008), Alabede (2009), Salehi (2009), Salehi and Naghilo (2009), Salehi and Moradi (2010), Appah (2011) stated that accounting firms provides a variety services that include taxation, auditing, book-keeping, valuation, actuarial, human resources, financial information systems designs and implementation etc. Hence, Alabede (2009) argues that the application of marketing concept will no doubt enhance the satisfaction of accounting clients and subsequently the performance of accounting firms.…”
Section: Introductionmentioning
confidence: 99%